1998
DOI: 10.1128/mcb.18.11.6213
|View full text |Cite
|
Sign up to set email alerts
|

MFR, a Putative Receptor Mediating the Fusion of Macrophages

Abstract: We had previously identified a macrophage surface protein whose expression is highly induced, transient, and specific, as it is restricted to actively fusing macrophages in vitro and in vivo. This protein is recognized by monoclonal antibodies that block macrophage fusion. We have now purified this protein and cloned its corresponding cDNA. This protein belongs to the superfamily of immunoglobulins and is similar to immune antigen receptors such as the T-cell receptor, B-cell receptor, and viral receptors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
131
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 49 publications
1
131
0
3
Order By: Relevance
“…[12][13][14] The spleen contains different types of macrophages, however, with each type residing in a specific region of the spleen and having a distinct function. 41,42 Most macrophages positive for the F4/80 antigen, which are thought to be responsible for phagocytosis and digestion of circulating RBCs, 5,6 are thus present in the red pulp area.…”
Section: Shps-1 Mutant Mice Manifest Anemia and Splenomegalymentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] The spleen contains different types of macrophages, however, with each type residing in a specific region of the spleen and having a distinct function. 41,42 Most macrophages positive for the F4/80 antigen, which are thought to be responsible for phagocytosis and digestion of circulating RBCs, 5,6 are thus present in the red pulp area.…”
Section: Shps-1 Mutant Mice Manifest Anemia and Splenomegalymentioning
confidence: 99%
“…[1][2][3] Src homology 2 domain-containing protein tyrosine phosphatase substrate-1 (SHPS-1), 7,8 also known as signal-regulatory protein ␣, 9 brain immunoglobulin (Ig)-like molecule with tyrosinebased activation motifs, 10 and p84 neural adhesion molecule, 11 is a transmembrane protein that is especially abundant in macrophages. [12][13][14] The putative extracellular region of SHPS-1 comprises 3 Ig-like domains, and its cytoplasmic region contains 4 tyrosine phosphorylation sites that mediate the binding of Src homology 2 domain-containing protein tyrosine phosphatases designated SHP-1 and SHP-2. 7,9 Tyrosine phosphorylation of SHPS-1 is regulated by various growth factors and cytokines as well as by integrinmediated cell adhesion to extracellular matrix proteins.…”
Section: Introductionmentioning
confidence: 99%
“…(13) Therefore, although the functions of osteoclasts and FBGCs differ, they express common molecules, such as DC-STAMP, that function in cell-cell fusion. (3) To date, various molecules have been identified that regulate fusion of osteoclasts or macrophages, including DC-STAMP, ATP6v0d2, CD47, CD44, CD9, CD81, MFR, E-cadherin, and meltrin-a (3,(14)(15)(16)(17)(18)(19)(20)(21) ATP6v0d2-deficient mice show significant reductions in fusion of either cell type. (21) DC-STAMP-deficient osteoclasts or FBGCs show a complete lack of cell-cell fusion, a function specific for macrophage lineage fusion, since fertilization and myotube formation is normal in DC-STAMP-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…One signal-regulatory protein, Src homology 2 domain-containing protein tyrosine phosphatase substrate 1 (SHPS-1) [19], is also known as signalregulatory protein a1 (SIRP a1) [20], BIT (brain Iglike molecule with tyrosine-based activation motifs) [21], P84 [22], MFR (macrophage fusion receptor) [23] and MyD-1 [24]. In mice, SHPS-1 is expressed in myeloid cells, including monocytes, macrophages and DC [25].…”
Section: Introductionmentioning
confidence: 99%